Structural Reforms and Regional Convergence - Spilimbergo, Antonio (IMF Working Papers; Working Paper ;, 2012)
Which structural reforms affect the speed the regional convergence within a country? We found that domestic financial development, trade/current account openness, better institutional infrastructure, and selected labor market reforms facilitate regional convergence. However, these reforms have mixed effects on the growth of regions closer to the country's development frontier. We also document that regional income disparity and average income are inversely correlated across countries so that speeding up regional convergence increases national income. We also present a theoretical model to discuss these results.